Spaces of democracy : geographical perspectives on citizenship, participation and representation - Barnett, Clive; Low, Murray (London ; Thousand Oaks : SAGE, 2004)
In an historically unprecedented way, democracy is now increasingly seen as a universal model of legitimate rule. Spaces of Democracy addresses the key question: How can democracy be understood in theory and in practise? In three thematically organised sections, Spaces of Democracy uses a critical geographical imagination (informed by thinking on space, place, and scale) to interrogate the latest work in democratic theory.
Cover; Contents; List of Contributors; Acknowledgements; Chapter 1 -- Geography and Democracy: An Introduction; Chapter 2 -- Global Democratization: Measuring and Explaining the Diffusion of Democracy; Chapter 3 -- Electoral Geography in Electoral Studies: Putting Voters in Their Place; Chapter 4 -- Representation, Law and Redistricting in the United States; Chapter 5 -- Citizens and the State: Citizenship Formations in Space and Time; Chapter 6 -- Open Borders and Free Population Movement: A Challenge for Liberalism; Chapter 7 -- Cities as Spaces of Democracy: Complexity, Scale and Governance.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Political participation; Democracy; Citizenship; Democracy; Participation politique; Démocratie.; Nationalité.; Citoyenneté.; democracy; citizenship; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Citizenship; Democracy; Political participation; Democratie; Ruimtelijke aspecten; Politieke geografie; Aspect géographique.; Citoyenneté; Démocratie.; Gouvernement représentatif.; Participation politique; Spaces; Spaces